2012
DOI: 10.3762/bjoc.8.247
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on β-cyclodextrin inclusion complexes with propiconazole and protonated propiconazole

Abstract: SummaryThe synthesis of the β-cyclodextrin/propiconazole nitrate inclusion complex and the advantages of the encapsulation of this drug were recently reported, but the experimental data only partially revealed the structure of the supramolecular complex due to the limitations in understanding the intermolecular association mechanism. The present work describes the equilibrium molecular geometries of β-cyclodextrin/propiconazole and β-cyclodextrin/protonated propiconazole, established by the AM1 and PM3 semi-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Prediction from the molecular docking method reduces time while increasing accuracy and precision in chiral recognition since it allows a quick screening of a large database for a potential chiral selector or drugs that would otherwise require tedious work in the laboratory . Binding energy difference, chiral recognition mechanism resulting from CDs guest inclusion complex, geometry, and the interaction energy of the inclusion complex can be elucidated by computer simulation methods, in which case molecular docking enables the prediction of the strength of association or binding affinity between two molecules using scoring functions …”
Section: Resultsmentioning
confidence: 99%
“…Prediction from the molecular docking method reduces time while increasing accuracy and precision in chiral recognition since it allows a quick screening of a large database for a potential chiral selector or drugs that would otherwise require tedious work in the laboratory . Binding energy difference, chiral recognition mechanism resulting from CDs guest inclusion complex, geometry, and the interaction energy of the inclusion complex can be elucidated by computer simulation methods, in which case molecular docking enables the prediction of the strength of association or binding affinity between two molecules using scoring functions …”
Section: Resultsmentioning
confidence: 99%
“…The higher the negative value of the binding energy, the more thermodynamically stable is the inclusion complex. 43 (2) Molecular modeling confirmed that IMQ was able to form an inclusion complex with βCD. The binding energy was 89.38 kcal mol -1 for IMQ ( Figure 6a) and 100.34 kcal mol -1 for IMQ + (Figure 6b).…”
Section: Molecular Modelingmentioning
confidence: 95%
“…Theoretical studies of interaction of cyclodextrins with drugs are an important aspect in the drug design and development 53 . Therefore, we decided to perform Density Functional Theory (DFT) calculation of interaction energy and binding energy of complex of selected thiazole derivative with b-cyclodextrin.…”
Section: Calculationmentioning
confidence: 99%